Qualidade de água como tema para a socialização do conhecimento científico em região semi-árida brasileira - Sodré Neto, Luiz (2008)
During the dry and rainy periods, in the Piranhas-Assu river hydrographic basin, variations in bacterioplankton and trophic state indexes were studied in the lotic and lentic environments. The means of total bacterial density wavered in the order of 107 organisms. mL-1 and they were higher in the rainy period. Cocci bacteria were numerically predominant in all sampling points, influencing the total abundance of bacterioplankton. Total bacterial biomass varied from 659 to 1997,3 µgC.L-1 due to the high values of filaments cellular volume. Total phosphorus amounted 108 µg.L-1 and it had a positive correlation with chlorophyll a (r = 0,94; p < 0,05) during dry period, when these variables presented higher concentrations. There wasn t a high spatial variation. The low transparency of water and the phosphorus and chlorophyll concentrations indicated eutrophic or hipereutrophic levels in studied points of reservoir. These variables, associated with high density and biomass values found, alert to the necessity of a constant monitoring of the semi-arid aquatic ecosystems, where the quality of water is affected by dry occurrence